Effect of Antibiotics Exposure on Gills, Liver, Kidney and Brain of Common Carp (Cyprinus carpio) - Waqar, Muhammad; Elahi , Usman; Masud, Samrah; Shahzadi, Sana; Yousaf, Sana; Hasaan, Ansa Ali (Indus Journal of Bioscience Research, 2025)
This work specifically assesses histopathological alterations in the organs of common carp (Cyprinus carpio) exposed to two frequently prescribed and broadly administered antibiotics, amoxicillin and metronidazole. Since these antibiotics affect human health, its effects on aquatic lives needs to be understood. Common carp samples of similar size and weight were randomly divided into three groups: the control group, another group treated with amoxicillin for 7 and 14 days, and the last group treated with metronidazole for 7 and 14 days. Usually the fish were treated with antibiotics at a concentration of 20 mg/L in their water for the duration stated. After exposure, the fish were killed and organs such as the brain, gills, liver, and kidneys were dissected out and processed for histopathological examination using the H&E staining. Diaphragmatic tissues were examined for histological alterations using light microcopy at 10x and 40x objectives and the quantitative analyses were performed with Image software. In the present study, statistical measurements were made by employing the software named as SPSS version 23.0 and analyzing nutrient through ANOVA. The investigation established marked histological alterations in the gill, hepatic, renal, and cerebrum tissues of the experimentally challenged common carp with either of the antibiotics at 7 and 14 days post-treatment. Stress response alterations several reins were observed under metronidazole treatment with significant differences (P<0.05) across all analyzed organs compared to amoxicillin. Thus, the particular impact of these antibiotics on common carp is exposed in regard to the main potential threat to aquatic environment and to human health due to fish consumption. Thus, the present work confirms the potential of amoxicillin and metronidazole to induce histological alterations, as well as showing that metronidazole is more toxic to common carp. Finally, these findings underscore the significance of responsible use of antibiotics that are used in fish production and beckon for constant surveillance of antibiotic remnants in water in order to completion the probable adverse effects on fish health and human beings. More studies are needed to capture the enduring impact of antibiotics on fish and the environment as well.